Prediksi Jumlah Pengiriman Paket Menggunakan Metode Auto Regressive Integrated Moving Average - Sholikah, Layla Hidayatus; Chandra, Novita Eka; Rohmaniah, Siti Alfiatur; Rohmah, Awawin Mustana (Jurnal Matematika, 2024)
This research aims to predict the number of postal office package deliveries using the ARIMA method. The data used is delivery data at the Lamongan Post Office from January 2018 to December 2022. The results of this research are the best model for predicting delivery data, namely ARIMA (2,2,0) with an RMSE value of 2333.897 and a MAPE value of 8,83%. Prediction results for the full year in 2023 have increased every month. Keywords: prediction, delivery, ARIMA